Chemical composition of the meat of “Nero Siciliano” pigs reared outdoor and plein air - L. Chiofalo; D. Piccolo; B. Chiofalo; A. Zumbo (Italian Journal of Animal Science, 2011)
Transformations occurred in animal production during the last 50 years have deeply influenced the national pork production system which, considering the progress in selective activity of some foreign races, has determined a process of substitution of old local races, some of which have disappeared and others in extinction, with a heavy loss of precious genetic material. The use of autochthonous races, some of which are living in absolute freedom, apart from providing high quality production and limiting importation, could also allow a wider and more rational exploitation of marginal areas...